Electrocatalyts: Controlled Fabrication of Hierarchically Structured Nitrogen‐Doped Carbon Nanotubes as a Highly Active Bifunctional Oxygen Electrocatalyst (Adv. Funct. Mater. 9/2017). (March 2017) - Zhao, Xianglong; Li, Feng; Wang, Ruining; Seo, Jeong‐Min; Choi, Hyun‐Jung; Jung, Sun‐Min; Mahmood, Javeed; Jeon, In‐Yup; Baek, Jong‐Beom
Abstract : A multi‐step synthesis approach for hierarchically structured nitrogen doped carbon nanotubes (NCNTs) is reported by Jong‐Beom Baek and co‐workers in article number 1605717. The walls are embedded uniformly with copper (Cu) nanoparticles and the outer wall surfaces are decorated with cobalt oxide (Co x O y ) nanoparticles. These Cu@NCNT/Co x O y composites demonstrate high electrocatalytic activity for both oxygen reduction reaction and oxygen evolution reaction.